Tachycardia-induced cardiomyopathy - Nakatani, Bruno Tsutomu [UNESP]; Minicucci, Marcos Ferreira [UNESP]; Okoshi, Katashi [UNESP]; Okoshi, Marina Politi [UNESP] (BMJ, 2012)
Tachycardia-induced cardiomyopathy (TIC) is an important cause of heart failure as it is potentially reversible after ventricular rate control. A 66-year-old hypertensive woman presented with a 15-day history of tachycardia, dyspnoea and oedema. ECG revealed atrial fibrillation with ventricular frequency of 130 beats per minute (bpm). Echocardiogram showed dilated left ventricle (LV) with 0.39 ejection fraction. Angiography revealed non-obstructed coronary arteries. Heart rate and cardiac failure were controlled with amiodarone, digoxine, captopril, metoprolol and furosemide. During follow-up, despite drug dose optimisation, the patient kept complaining of tachycardia and dyspnoea with a ventricular rate between 108 and 120 bpm. Medical staff suspected she was not taking her medicines properly. Two months later, the patient was asymptomatic and had converted to sinus rhythm (heart rate of 76 bpm). Echocardiogram showed normal LV size and function. Patient 's diagnosis was TIC. Although rare, TIC should be considered in all cases of systolic dysfunction associated with tachyarrhythmia. Copyright 2012 BMJ Publishing Group. All rights reserved.
Keywords: amiodarone; captopril; digoxin; furosemide; metoprolol; aged; angiocardiography; case report; differential diagnosis; dyspnea; edema; electrocardiogram; female; follow up; heart atrium fibrillation; heart failure; heart left ventricle ejection fraction; heart rate; human; hypertension; outcome assessment; priority journal; sinus rhythm; tachycardia; tachycardia induced cardiomyopathy